2023
DOI: 10.3991/ijim.v17i03.36325
|View full text |Cite
|
Sign up to set email alerts
|

Survey Analysis of Students and Teachers' Perceptions of E-Learning and M-Learning in Morocco

Abstract: With the advent of new technologies, smart devices, and the evolution of ICT in education, the integration of new technologies into learning systems has been mandated and a new way of learning has been born. E-learning and m-learning provide learners with great opportunities anytime, anywhere without restrictions. A new generation of students has grown up with technology and can be easily identified through smart devices. We discuss the identity of e-learning and m-learning; conduct a survey analysis to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Compared to other technology devices like laptops, smartphones are more affordable, easy to carry, and adequate for online learning. Students can easily access learning material, interact with it, and increase their engagement with e-learning (Dehbi et al, 2023). Teachers also found mobile learning potentially helpful in creating online education courses through the platform.…”
Section: Perceived Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other technology devices like laptops, smartphones are more affordable, easy to carry, and adequate for online learning. Students can easily access learning material, interact with it, and increase their engagement with e-learning (Dehbi et al, 2023). Teachers also found mobile learning potentially helpful in creating online education courses through the platform.…”
Section: Perceived Benefitsmentioning
confidence: 99%
“…This affordability makes mobile learning accessible to a broader range of students, regardless of socioeconomic background. Dehbi et al (2023) highlight the costeffectiveness of mobile learning devices, noting that they provide students with an affordable and convenient means of accessing educational content. As a result, students can easily interact with learning materials, participate in online discussions, and engage in context-sensitive learning activities.…”
Section: Perceived Benefitsmentioning
confidence: 99%
“…E-learning apps significantly enhance student engagement in the learning process [15]. A survey of university students revealed that 78% reported feeling more engaged in their coursework using e-learning apps [16]. According to a survey the authors took in [16] to explore students' and teachers' interest in e-learning and mobile learning, they argue that the field of mobile learning is expanding.…”
Section: Overviewmentioning
confidence: 99%
“…A survey of university students revealed that 78% reported feeling more engaged in their coursework using e-learning apps [16]. According to a survey the authors took in [16] to explore students' and teachers' interest in e-learning and mobile learning, they argue that the field of mobile learning is expanding. Thus, virtual reality, IoT architecture and smart learning have great potential for mobile learning.…”
Section: Overviewmentioning
confidence: 99%